Leaf wax isotopes reveal distinct hominin paleoenvironments in the Eastern Qinling Mountains of central China. (1st January 2023) - Fox, Mathew L.; Tierney, Jessica; Lu, Huayu; Wang, Shejiang; Xia, Wenting; Zhang, Hongyan; Wu, Jiang
Abstract: Here, we present the first leaf wax record in association with Paleolithic occupations in the Eastern Qinling Mountains of central China. This region has been the focus of numerous archaeological projects, as it contains evidence of some of the oldest (∼2.0–1.2 Ma) hominin occupations in eastern Eurasia and is one of the key areas yielding bifacial handaxe technology. Previous research demonstrates that these mountains represent a physio-geographic barrier that separates the semi-arid north from the sub-tropical south and defines northern and southern Paleolithic industries. Although evidence suggests models associated with the Qinling Mountains need refinement, our results demonstrate that there are observable differences between the southern and northern Qinling Mountains and are in good agreement with previous observations. Here, we use the carbon isotopic values (δ 13 C) of leaf wax lipids to reconstruct the ratio of C3 to C4 vegetation at long-term Pleistocene Homo erectus occupations of the Hanzhong and Luonan Basins of the Eastern Qinling Mountains. In Hanzhong, isotopic range is low (1.5‰) and vegetation was dominated by C3 vegetation (85–90%) throughout the middle to late Pleistocene. Paleolithic technologies associated with these stable vegetation regimes are dominated by expedient Mode I technologies throughout the entire record. Conversely, in Luonan, isotopic range is significantly higher (4.2‰) and C4 vegetation increases to approximately 40% during some periods, which represents the expansion of forest-grassland mosaics. These fluctuating vegetation regimes are also associated with the emergence of Mode II bifacial technology, suggesting variable environments triggered the need for multifunctional handaxe technology. Our research demonstrates that there are key differences between the southern and northern Qinling Mountains, and that the northern Qinling Mountains are associated with both forest-grassland mosaics and less expedient technologies. Finally, in both basins our records demonstrate that patterns in C3 :C4 track Marine Isotope Stages and appear to operate on interglacial-glacial timescales. Highlights: Leaf wax isotopes reveal distinct habitats in the Qinling Mountains of China. More variable environments are associated with handaxes. Asian monsoons are tied to patterns in local vegetation.